2019
DOI: 10.1051/bioconf/20191204008
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates: Potential sources and control measures

Abstract: The issue of endocrine disruptors is a subject of debate in the agri-food sector and questioning for consumers through the media. Among these compounds, some of the family of phthalates, are used in the composition of some materials used in wineries. This makes it a worrying issue in terms of image and safety. The objective ok this work was to identify the sources of phthalates and the factors favoring their diffusion in wines to propose preventive and curative solutions to the wine makers. The modalities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Russo et al detected DBP, BBP, and DEHP in six commercial wines packed in glass bottles and Tetrapak box and a sample of home-prepared red wine [ 191 ]. In addition, 11 commercial wine samples were analyzed and were found highly contaminated [ 198 , 199 , 200 ].…”
Section: Occurrence Of Paes In Foodmentioning
confidence: 99%
“…Russo et al detected DBP, BBP, and DEHP in six commercial wines packed in glass bottles and Tetrapak box and a sample of home-prepared red wine [ 191 ]. In addition, 11 commercial wine samples were analyzed and were found highly contaminated [ 198 , 199 , 200 ].…”
Section: Occurrence Of Paes In Foodmentioning
confidence: 99%
“… Aghaziarati et al (2020) found that whisky samples have a higher level of PE than the beer samples. The alcohol content is a major factor in the migration of phthalates from package materials, tubbing and other equipment in the production process, probability due to their high solubility in ethanol ( Grinbaum et al, 2019 , Jurica et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is of notice that, the only non-alcoholic beer sample with a positive result for the presence of phthalate-adipate is from a commercial brand, once again pointing to an environmental contamination, since there is no alcohol content to aid in the compounds migration to the sample. Notwithstanding, alcohol content is a major factor in phthalate contamination ( Grinbaum et al, 2019 ), as all positive sample but one, are alcoholic. Still, it must be taken into consideration that these samples were from different batches with different production and expiration dates, which may also explain the different results.…”
Section: Resultsmentioning
confidence: 99%
“…The method has higher LOD than that of [ 39 ] (0.4 > 0.002–0.03 μg/L) ( Table 6 ). However, observation of the phthalate content commonly found in samples or released during migration studies, shows that the LOD of the method is sufficient for this analysis [ 15 , 40 , 41 ]. Methods with a limit of detection lower or higher than the PAE contents encountered in the samples could imply high dilution or concentration of these, which could increase the uncertainties of the results.…”
Section: Resultsmentioning
confidence: 99%
“…The phthalate content increases rapidly in hot pap for the first 40 min, then increases very slightly. This high migration during the first minutes is related to phthalates from the surface of the bucket, that diffuse rapidly in contact with food [ 40 ]. The low migration speed after 1 h could be related to the structure of the plastic polymer (formulation additives) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%